Digital Acro-osteolysis Revealing Hajdu–Cheney Syndrome in an Elderly Patient: A Case Report - Antonio GARCÍA-JIMÉNEZ; Lluis POMEROL; Eulàlia ARMENGOL (The Journal of Hand Surgery (Asian-Pacific Volume), 2026)
Hajdu–Cheney syndrome (HCS) is a rare genetic connective tissue disorder characterised by progressive acro-osteolysis of the distal phalanges, pseudo-clubbing, joint hyperlaxity and generalised osteoporosis. We report the case of an 85-year-old woman presenting with infectious dactylitis of the third finger of the right hand, in whom radiographs revealed distal osteolysis in several digits. After excluding infectious, inflammatory and metabolic causes, genetic testing confirmed a heterozygous NOTCH2 mutation consistent with HCS. This case highlights the importance of recognising the characteristic radiographic and clinical findings in the hand, since its presentation may mimic rheumatologic or infectious conditions. Awareness of this entity allows accurate diagnosis, avoidance of unnecessary surgical interventions and optimised functional and preventive management. Level of Evidence: Level V (Therapeutic)